ANESTHETIC MANAGEMENT OF A PREGNANT PATIENT WITH WOLFF PARKINSON WHITE SYNDROME UNDERGOING CAESARIAN SECTION - Wirahadi, Dhanu Enggar; EM, Tjahya Aryasa; Labobar, Otniel Adrians (HEARTY, 2025)
Abnormal electrical conduction via an auxiliary channel (Kent's Bundle) causes Wolff-Parkinson-White (WPW) syndrome, a congenital cardiac preexcitation disease that can result in symptomatic and sometimes fatal arrhythmias. It occurs in 0.9-3% of the general population. Because of changes in hemodynamics, hormones, the autonomic nervous system, and emotions, pregnancy raises the risk of supraventricular tachycardia (SVT). A 29-year-old woman with G2P1001 gestational age 39 weeks, history of Caesarean Section (C-Section) 1 time with WPW Syndrome and history of SVT underwent C-Section and tubectomy with low dose spinal anesthesia. The patient has a history of palpitations and the EKG shows WPW pattern. Vital signs, physical examinations and laboratorium findings within normal limits. Echocardiography with the results of normal cardiac chamber dimensions, global normokinetic, Ejection Fraction 68%, normal diastolic function, normal right ventricle contractility TAPSE 2.0 Cm, valves within normal limits, ERAP 8 mmHg, Interatrial and interventricle septum impression intact, no PDA seen. This patient, diagnosed with WPW syndrome at moderate risk due to a history of SVT, could not undergo ablation due to limited facilities and pregnancy contraindications. Bisoprolol was used for treatment of transient palpitations. Preoperative fluids achieved a diuresis target of 1.1 cc/kg/hour to avoid hypovolemia and tachycardia. Regional anesthesia was chosen for cesarean section to reduce sympathetic activity, with careful attention to preventing high-level blocks. A subarachnoid block with low-dose bupivacaine (7.5 mg) and fentanyl (25 mcg) provided stable hemodynamics and effective anesthesia. A healthy baby was delivered with an APGAR score 8/9, and postoperative analgesia was optimized. Regional anesthesia is the choice for c-section with WPW syndrome, the use of low doses of bupivacaine heavy combined with adjuvant fentanyl produces good quality block with rapid onset and without hemodynamic instability.